Comment on Timely deposition of macromolecular structures is necessary for peer review by Joosten et al. (2013). (1st December 2013) - Berman, Helen; Kleywegt, Gerard J.; Nakamura, Haruki; Markley, John L.
<x xml:space="preserve">Abstract</x> The wwPDB responds to the article by Joosten et al. [(2013), Acta Cryst. D69, 22932295].